Some realizations and instances of Yager prioritized preference frame with application in evaluation and decision making. Issue 3 (6th January 2020) - Yang, RouJian; Pu, XingTing; Mesiar, Radko; Yager, Ronald R.; Jin, LeSheng
Abstract: This study first revamps Yager prioritized ordered weighted averaging operators, and condenses them into a conceptual frame with putting aside one realization from Yager's original proposal. Then, based on elicited conceptual frame called Yager prioritized preference conceptual frame, this article proposes three distinct realizations to the conceptual frame with corresponding different instances, in which some evaluation models with weights determination methods are provided. Numerical examples are also presented immediately after every instance. Lastly, this study proposes the concepts of outer monotonic, inner monotonic, and global monotonic weights functions, and discusses some related properties, which are often embodied in preferences of decision makers.